VYDŪNAS ABOUT F. M. DOSTOEVSKY’S WORKS - Варлашина, Маргарита (Literatūra, 2013)
The article deals with an analysis of the Lithuanian writer and philosopher Vydūnas’ small text “F. M. Dostoevsky” (1921), intended for this writer’s 100th birthday anniversary. The philosopher supposes that it is inappropriate to read this deeply Russian writer’s works. His conclusion Vydūnas explains in the second paragraph. According to him, Dostoevsky’s works do not reveal the true faith, wisdom and power, do not give a person the opportunity to express the human grandeur. The most important Russian writer’s error refusal to identify the an is his example of a perfect human life. Vydūnas completes the anniversary article with the tasks set to the Lithuanian people in accordance with moral norms (“to look forward and up”). This paper discusses the negative Vydūnas’ approach to Dostoevsky’s works, interpretes the causes which led to rejecting the Russian writer’s value to the Lithuanian culture. Vydūnas linked the creative value with the problem of nationality and national spirit dissemination. Dostoevsky‘s works for Vydūnas are the Russian culture metonymy. It is argued that the critical approach of Vydūnas’ to Dostoevsky’s works was determined by: 1) a unique religious philosophical Vydūnas’ world system formed of Protestantism, German idealistic philosophy, neovedantism, theosophy, 2) Lithuanian historical political situation in the early twentieth century decades. Vydūnas’ article about Dostoyevsky expressed the then prevailing creative mood of Lithuanian intellectuals, a specific historical period, historical context.